EFEKTIVITAS TERAPI REMINISCENCE DALAM MENGURANGI DEPRESI PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN TAHUN 2024 - Deddy Sepadha Putra Sagala; Ali Sabela Hasibuan; Anita Sri Gandaia Purba; Yuni Suharnida Lubis; Arfah May Syara; Yokhebed Agatha Eka Rista Ziliwu; Sarida Surya Manurung (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
Chronic kidney failure is a non-communicable disease caused by a decrease in the ability of the kidneys to carry out their functions. Hemodialysis therapy is a therapy given to sufferers of chronic kidney failure which functions to replace the work of the kidneys using a dialysis machine. Hemodialysis procedures performed on kidney failure patients are likely to cause depression because sufferers undergoing hemodialysis may experience feelings of discomfort or depression due to weakness in their physical condition and dependence on dialysis machines throughout their lives. The aim of this study was to determine the effectiveness of reminiscence therapy in reducing depression in chronic kidney failure patients undergoing hemodialysis at Imelda Pekerja Indonesia Hospital. This type of research is quantitative research, with the Quasy Experiment method, and with a pre-test and post-test group research design. This research was conducted in April – July 2024 in the Hemodialysis Room at Imelda Pekerja Indonesia Hospital, Medan. This research uses a non-probability sampling technique using a purposive sampling method, namely using inclusion criteria in determining the sample, so that the total research sample is 20 respondents. The instrument used in this research is a questionnaire that refers to the Beck Depression Inventory (BDI-II) to determine depression status. Data analysis used univariate and bivariate analysis with the Wilcoxon test in the SPSS application. The results of the Wilcoxon statistical test showed a significant (p) value of 0.000 (p < 0.05), meaning that there was an effect of giving reminiscence therapy on depression status or in other words reminiscence therapy was effective in reducing depression in chronic kidney failure patients undergoing hemodialysis at Imelda Pekerja Indonesia Hospital, Medan.